The research on work engagement: theoretical aspects and the results of researches in the company operating in the IT sector = Badanie zaangażownia w pracę: aspekty teoretyczne i rezultaty badań w firmie działającej w sektorze IT - Wójcik-Karpacz, Anna (Zielona Góra: Faculty of Economics and Management Press)
The aim of this article is to exemplify the results of researches on work engagement in the company operating in the IT sector. The research methodology includes the studies of scientific literature and the quantitative method (survey questionnaire). The sample in the study comprises 509 employees of a company operating in the IT sector. Work engagement was measured with of the original 17-item Utrecht Work Engagement Scale (UWES).
Keywords: zaangażowanie w pracę; zaangażowanie pracowników; sektor IT; UWES; Utrecht Work Engagement Scale; work engagement; engaged employees; IT sector